PENGARUH PEMBERIAN KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA ALPHA HOTEL PEKANBARU - Eni Setianingsih; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was conducted at Alpha Hotel Pekanbaru, Jalan Imam Munandar No. 17. North Tangkerang, Kec. Bukit Raya, Pekanbaru. The purpose of this research is to determine the effect of compensation and work environment on employee job satisfaction at Alpha Hotel Pekanbaru simultaneously and partially. In this research, the method used is descriptive and quantitative analysis. Data management techniques use SPSS version 25.0. Sample in this research took a population of employees who worked in the company as many as 48 respondents. To determine the sample using the census/ sampling total method. Data collection techniques through questionnaires using questionnaires, types and sources of data using primary and secondary data. The measurement technique using a Likert scale. From data analysis which includes validity test, reliability test, multiple linear analysis, determination analysis and significance test with f (simultaneous) and t (partial) test. The results of the research show that giving compensation and work environment have an effect on job statisfactions, simultaneously this research has an effect. Partially, giving compensation has no effect on job satisfaction and the work environment has a significant effect on job satisfaction. Keywords: Giving Compensation, Work Environment, Job Satisfaction